Conversational Implicature Function between Mitsubishi Car Salesperson and Consumers in Padang - Betari Anindya; Ike Revita; Gusdi Sastra (Langkawi: Journal of The Association for Arabic and English, 2019)
Implicature is one of the important language studies. It is because implicature can provide explanations of linguistic facts that cannot be explained by other linguistic theories. Research on conversational implicature between Mitsubishi Car Salesperson and consumers in Padang is interesting to do to see linguistic phenomena that occur in the commercial environment, especially in the aspects of implicature. This study aims at explaining the function of implicature found in conversations between Mitsubishi car salesperson and consumers in Padang. The data in this study are the utterances containing implicature h between Mitsubishi car salesperson and consumers in Padang. Data were collected by using the observational method. This method was realized by using basic techniques and advanced techniques. The basic technique used is recording. While the advanced used is non-participate observation, recording, and note-taking s. Based on the results of the analysis, there are three pragmatic functions in the conversation of Mitsubishi car salesperson with consumers in Padang.  They are 1) assertive functions such as stating; explain, and express opinions. 2) directive functions such as demanding. 3) commissive functions such as advocating, promising, and offering. From the several implicature functions above, the most dominant function is assertive for stating, explaining, and expressing opinions. Some of these conversational functions tend to be used as expressing and explaining.